The Path to Ecotourism Intention: The Interplay of Ecotourism Attitude, Eco-Destination Image, and Environmental Belief (International Journal of Scientific Research and Management (IJSRM), 2025)
Drawing on the Value-Belief-Norm (VBN) theory, this study examines the mechanisms through which ecotourism attitude, eco-destination image, and environmental belief shape ecotourism intention. Data were collected from a sample of 410 international tourists visiting Loango National Park in Gabon and analyzed using structural equation modeling. The results reveal that ecotourism attitude positively influences ecotourism intention and eco-destination image. Eco-destination image also significantly affects ecotourism intention and mediates the relationship between ecotourism attitude and ecotourism intention. Furthermore, environmental belief moderates the link between ecotourism attitude and ecotourism intention, strengthening this association among individuals with stronger pro-environmental values. The study offers theoretical insights and practical implications for promoting ecotourism in emerging market contexts.